Thank you for donating: a survey of Australian donorsʼ and nondonorsʼ orientations toward noncash incentives for blood donation. Issue 7 (27th April 2020) - Van Dyke, Nina; Chell, Kathleen; Masser, Barbara; Kruse, Sarah P.; Gemelli, Carley N.; Jensen, Kyle; Davison, Tanya E.
Abstract : BACKGROUND: The aim of this study was to understand Australian donorsʼ and nondonorsʼ orientations toward 13 noncash incentives for blood and plasma donation and the associations between orientations and intention to donate (nondonors) and subsequent donation (donors). STUDY DESIGN AND METHODS: A survey of 1028 donors and 1201 nondonors was conducted online and by telephone. Donors were randomly selected from the Australian Red Cross Lifeblood donor panel; nondonors were selected from randomly generated fixed line and mobile telephone numbers across Australia. Incentives were chosen to reflect a wide array of possible noncash incentives that might be introduced by blood donation organizations (BDOs). Differences between donors and nondonors, as well as other subgroups, were investigated. RESULTS: Orientations toward most types of incentives were positive or neutral. No significant differences were observed between incentive orientations for whole blood versus plasma donations. Many subgroup differences were small but statistically significant. There were mostly small, positive, significant associations between nondonorsʼ intention to donate and orientations toward noncash incentives; there were mostly no significant associations between donorsʼ orientations and subsequent donation behaviors. CONCLUSION: The findings from this study suggest that BDOs that wish to trial noncash incentives in voluntary nonremunerative systems can be confident that neither donors nor potential donors will react negatively. They also indicate that BDOs have some flexibility in deciding which incentives to trial.